2015
DOI: 10.12693/aphyspola.128.b-23
|View full text |Cite
|
Sign up to set email alerts
|

Flexural Strength Reduction in Cemented Carbides

Abstract: Cemented carbides are hard materials used in tough materials machining as well as in situations where other tools would wear away. These are one of the most successful composite engineering materials ever produced. The advantage of cemented carbides is that their structure and composition can be engineered to have properties tailored to specific applications and operations. These materials allow faster and more precise machining and will leave a better surface finish. Carbide tools can also withstand higher te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…Recent research on chromium carbide stressed their resistance to oxidation and corrosion and suggested that they have great potential to replace hard chrome electroplating as protective coatings [3,4]. The chromium carbide layers can be obtained by physical vapor deposition (PVD) [5,6] or thermo-reactive deposition/diffusion (TRD) technology [7,8]. In the case of PVD thickness is much less than 10 µm making those unfit also withstood the high contact pressure and further adhesion to the substrate is less than that obtained with other types of coating techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research on chromium carbide stressed their resistance to oxidation and corrosion and suggested that they have great potential to replace hard chrome electroplating as protective coatings [3,4]. The chromium carbide layers can be obtained by physical vapor deposition (PVD) [5,6] or thermo-reactive deposition/diffusion (TRD) technology [7,8]. In the case of PVD thickness is much less than 10 µm making those unfit also withstood the high contact pressure and further adhesion to the substrate is less than that obtained with other types of coating techniques.…”
Section: Introductionmentioning
confidence: 99%